2017
DOI: 10.1097/md.0000000000008020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of intravesical electrical stimulation on detrusor underactivity

Abstract: The aim of this study was to retrospectively evaluate the effectiveness of intravesical electrical stimulation (IVES) on detrusor underactivity (DU).From 2009 to 2016, a total of 105 patients with symptoms of DU who were treated with IVES were included in this retrospective study. The medical records, physical examination findings, urine culture results, and video-urodynamic studies were reviewed. Changes in post-void residual urine (PVR) and voiding efficiency (VE) were included for evaluation of efficacy. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
10
1
1
Order By: Relevance
“…showed that IVES can improve PVR in patients with detrusor underactivity [13,23]. In our previous single‐centre pilot study, we also observed that IVES can effectively reduce PVR and improve BVE in patients with detrusor underactivity [17]. Improvement of BVE in the trial group was also significantly better than that in controls after 4 weeks of treatment.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…showed that IVES can improve PVR in patients with detrusor underactivity [13,23]. In our previous single‐centre pilot study, we also observed that IVES can effectively reduce PVR and improve BVE in patients with detrusor underactivity [17]. Improvement of BVE in the trial group was also significantly better than that in controls after 4 weeks of treatment.…”
Section: Discussionmentioning
confidence: 65%
“…The main efficacy index of this clinical trial was change of PVR compared with baseline at 4 weeks of treatment. According to our previous study, we expected the change of PVR from baseline in the trial group to be 150 mL at 4 weeks of treatment, and change of PVR from baseline in the control group was 40 mL at 4 weeks, with a standard deviation of 150 mL [17]. PASS 11.0 software was used for sample size estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Ez történhet a tibialis ideg bőrön keresztüli ingerlésével, kiegészítve a medencefenék izmainak stimulációjával. A hólyagon belüli (intravesicalis) stimuláció a hólyagkapacitás növelése és a hólyagürítés javulása révén lehet kedvező hatású [38].…”
Section: Invazív Kezelési Módokunclassified
“…However, urgency urinary incontinence did not significantly change. In a retrospective study of 89 patients with UAB stimulation sessions were performed 5 days a week for 30 mins until bladder function was normal or no further improvement was achieved 25. Stimulation parameters were as follows: 1–30 mA pulse amplitude, 10–25 Hz pulse frequency, and a 200–800 µs pulse width.…”
Section: Non-approved Modes Of Electrical Stimulation In the Treatmenmentioning
confidence: 99%